Whatisthe Difference Between Organizational Culture and Organizational Climate? A Native's Point of View on a Decade of Paradigm Wars - Denison, Daniel R. (Academy of Management Review, 1996)
Daniel R. Denison, What is the Difference between Organizational Culture and Organizational Climate? A Native's Point of View on a Decade of Paradigm Wars, The Academy of Management Review, Vol. 21, No. 3 (Jul., 1996), pp. 619-654